(untitled) (American Journal of Pedagogical and Educational Research, 2023)
An important aspect of technical progress is the loss of mass in the use of effective material, in this case it is necessary to send porous fillers to them. The use of lightweight concrete reduces the mass of the building structure by 35%, and cement by 10%. In this situation, the size of the structure increases, and its thermotechnical and acoustic properties are improved. In the last 10 years, a lot of research and studies have been carried out on the selection of composition, stability of lightweight concrete in porous aggregates.